Imaging with Electromagnetic Spectrum Applications in Food and Agriculture - Manickavasagan, Annamalai; Jayasuriya, Hemantha (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book demonstrates how imaging techniques, applying different frequency bands from the electromagnetic spectrum, are used in scientific research. Illustrated with numerous examples this book is structured according to the different radiation bands: From Gamma-rays over UV and IR to radio frequencies. In order to ensure a clear understanding of the processing methodologies, the text is enriched with descriptions of how digital images are formed, acquired, processed and how to extract information from them. A special emphasis is given to the application of imaging techniques in food and agriculture research.